AAR425: Introduction to Photography / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2018)
This course covers the study in photography and digital imaging. It deals with the basic knowledge of the mechanisms of camera, processes of developing the film until the final stage of presenting and mounting of the image. Creative imaging techniques will be introduced.